Do Job Training and Work Discipline Matter to Employee Performance in PT TASPEN (Persero) - Siska, Elmira; Razan, Aqilah Rahmah (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Human resources are not interchangeable with other manufacturing components, the most important and strategic role lies in the workforce used to the goals of the organization. The objective of the current research is to investigate how PT TASPEN (Persero) employee performance is influenced by work discipline and job training. The data collection technique uses a questionnaire that was distributed to 80 employees at PT TASPEN during April – May 2024. This study employed quantitative statistical analysis methods. Data processing using the SPSS tool. Data processing starts with instrument testing, which includes validity and reliability evaluations. The data was then submitted to a series of classical assumption tests. The t-test and F-test are used to test the hypothesis that has been developed. The partial test (t-test) indicates that job training has a positive and substantial impact on employee performance at PT TASPEN, with a computed t value > t table or 5.178 > 1.66724 and a sig value of 0.000 < 0.05. Work discipline partially has a positive and significant effect on employee performance at PT TASPEN with a computed t value > t table or 5.270 > 1.66724 and a sig value is 0.000 < 0.05. Simultaneously, (- test), job training and work discipline influence employee performance with a calculated F value of 147,396 > F table 2.35 and sig value of 0.000 < 0.05.